Analysis of Post-Paddy Fields into Red Chili Cultivation Land in Aek Paing Village Rantau Utara District Labuhanbatu - Engkih Pratama; Yusmaidar Sepriani; Badrul Ainy Dalimunthe; Kamsia Dorliana Sitanggang (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Some communities or farmers in North Rantau Sub-district who do not know how to use land or use land for something of higher economic value. A post-rice field land is the most appropriate idea or mindset in the field, by utilizing agricultural land it becomes more useful by providing knowledge about the chemical properties of paddy fields and providing insight that paddy fields require maximum handling, restoration and improvement so that land is productive in agriculture. chili cultivation, so that it can have a good influence on the economy of the surrounding community. This study aims to determine the chemical properties of the soil to utilize red chili plants in Aek Paing Village, Rantau Utara District, Labuhanbatu Regency. This research was carried out in post-rice fields located in Aek Paing Village, Rantau Utara District, Labuhanbatu Regency. The research was carried out on October 18, 2021 until it was completed. The method used in this research is using the free grid survey method. The results of this study found that post-rice fields located in the District of North Rantau, Labuhanbatu Regency, were not well used as red chili farming land. The results of this study indicate that the pH value is low, C-Organic is low, N-total is low, P-Bray II is high, Ca is low, Mg is low, K is high, Na is low, CEC is high.